L’entrepreneurialisme urbain comme mode d’animation : l’espace public madrilène disputé - Valentin Clavé-Mercier (Ambiances)
This paper questions the urban entrepreneurialism as a hegemonic mode of animating public space. It does so by observing the daily social, political and material reality of two public squares in downtown Madrid: Plaza del Dos de Mayo and Plaza Luna. On the basis of a study of spontaneous and ritualised practices, legal, a-legal or illegal and political or daily ones, this paper highlights the existing conflicts relating to entrepreneurial animation of public space. Building on the analysis of several senses of place constructed and experienced by the groups that were studied, I sketch the outlines of efforts aimed at re-signification of these public squares. First, I describe different entrepreneurial dynamics that can be observed in the studied territory and linked to public space management. I also question their basic goals. Then, I reconstruct the senses of place that exist for the two public squares. This process allows the unveiling of opposed urban imaginaries and several ways in which the entrepreneurial mode of animation is contested. Finally, this paper addresses the consequences of exponential development by entrepreneurial dynamics in these two public squares, but also the stakes they represent for Madrid downtown urban renewal, governance and urban life.